Removable prosthesis with precision attachments for the lower jaw in lateral edentation - Lucia Alexandra Draghici; Tudor Ionescu; Teodora Maria Pangica; Dorin Alexe (Romanian Journal of Stomatology)
Background. In certain cases of lateral edentation, some treatment options are limited due to the patient’s desire or maybe due to the fact that biology could not permit otherwise. Hence, in these scenarios the options to use the implant therapy are limited. Case report. 50-year-old female patient was referred to clinic for a full mandibula rehabilitation. In this case the patient was diagnosed with Kennedy Class I. In this situation, the treatment option was fixed metal-ceramic crowns with precision attachments (keyway attachments) for a removable prothesis. Aim. To emphasize the fact that, from a socio-economic point of view, the patient tends to choose the more accessible treatment option, but also the time component has a major impact on the choice they make, the development time of a treatment plan being very important to the patient. Material and methods. 10 cases of partial edentation were analyzed for the possibility of realizing two treatment plans, namely the version with implants or with removable prosthesis. The clinical implications of various aspects of this area were monitored and displayed as results. Results. Patients were much more receptive to the removable prosthesis with precision attachments treatment compared to the insertion of implants. The former has a similar result to the latter, but in a much shorter time span and with lower costs. Conclusions. From the analyzed it was confirmed that edentulous patients can be successfully treated with fixed prosthodontics associated with a removable partial prosthesis with precision attachments with the same benefits that the implant works might have brought them, the patient being satisfied with the quality of life gained as a result of benefitting from removable prosthesis in a relatively convenient period of time.